Vaginitis. Extending the diagnostic spectrum - Saona Ugarte, Pedro (2015)
Vaginitis diagnosis is usually associated to bacterial vaginosis, Trichomonas vaginalis or Candida albicans. Nevertheless these are not the only causes of vaginal discharge, the most frequent vaginitis symptom. In this report we present other less frequent causes of vaginal discharge. Cases of vaginitis in the child are usually secondary to vulvar dermatologic problems. The presence of foul smelling bloody discharge may be by vaginal foreign body. Most frequent bacteriae producing vaginitis in children are Hemophilus influenzae, group A Streptococcus and Escherichia coli. Treatment should be oriented to the problem cause. In the pre and post menopause woman the discharge may be due to atrophic vaginitis or descamative inflammatory vaginitis. In relation to treatment in the first case the use of topic or systemic estrogens is recommended and in the second, the use of clindamycin 2% in vaginal cream. One cause of discharge could be cervicitis and the pathogenic agents Chlamydia trachomatis and Neisseria gonorrhoeae. Recommended treatment would be azitromycin or doxycycline and ceftriaxone or ciprofloxacin.